2022
DOI: 10.31635/ccschem.022.202101661
|View full text |Cite
|
Sign up to set email alerts
|

Simple Double Hetero[5]helicenes Realize Highly Efficient and Narrowband Circularly Polarized Organic Light-Emitting Diodes

Abstract: Helicene-based emitters with unique inherent circularly polarized luminescence (CPL) are promising yet remain a formidable challenge for highly efficient circularly polarized organic light emitting diodes (CP-OLEDs), ascribed to their tough synthesis, low emission efficiency, and easy racemization in thermal deposition process. Herein, a pair of helicene-based enantiomers, namely (P)-helicene-BN and (M)-helicene-BN, were developed, which merge helical chirality and the B/N/S inserted polycyclic aromatic frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…11), characterized by a B/N/S embedded polycyclic fused aromatic skeleton. 54 P / M - helicene-BN displayed obvious MR-TADF and CPL properties. The CP-OLEDs emitted green EL ( λ EL = 520 nm) with a narrow FWHM of 49 nm, extremely high EQE max of up to 31.5%, as well as CPEL signals with | g EL | of 2.2 × 10 −3 .…”
Section: Chiral Tadf Molecules Based On An Intrinsic Chirality Strategymentioning
confidence: 99%
“…11), characterized by a B/N/S embedded polycyclic fused aromatic skeleton. 54 P / M - helicene-BN displayed obvious MR-TADF and CPL properties. The CP-OLEDs emitted green EL ( λ EL = 520 nm) with a narrow FWHM of 49 nm, extremely high EQE max of up to 31.5%, as well as CPEL signals with | g EL | of 2.2 × 10 −3 .…”
Section: Chiral Tadf Molecules Based On An Intrinsic Chirality Strategymentioning
confidence: 99%
“…Apart from RISC acceleration via the heavy‐atom effect of S atoms, intriguing chiroptical properties based on the helical nature of S‐bridged MR frameworks were recently found. [ 96,102 ] In 2022, Chou and co‐workers reported two CPL‐active MR‐TADF emitters, BN4 and BN5 [ 96 ] (Figure 7), which exhibited narrowband green TADF emissions (λ PL = 500/497 nm, FWHM PL = 43/44 nm, and Φ PL = 88%/87%, respectively, in toluene) with relatively high k RISC values of ≈10 5 s −1 . Because of the sufficient racemization barriers induced by the asymmetrical peripheral lock, the separation of enantiomers into (−)( P , P′ , P″ )‐ and (+)( M , M′ , M″ )‐atropisomers was possible.…”
Section: Multi‐heteroatom Mr‐tadf Materialsmentioning
confidence: 99%
“…Most recently, MR-TADF materials containing S atom(s), a third-period element, have received particular attention. [83,[94][95][96][97][98][99][100][101][102][103] This is primarily because the incorporation of heavier S atom(s) facilitates spinflip RISC via the heavy-atom effect in several D-A type TADF materials. [24,[104][105][106] The first S-doped MR-TADF materials, BSBS-N1 [94] and 2PTZBN [95] (Figure 7), were reported by Yasuda's group and Yang's group, respectively, around the same time in 2021.…”
Section: B/n/s(se) Systems With Heavier Chalcogensmentioning
confidence: 99%
“…However, due to the cotton Yang et al reported a pair of helicene-based enantiomers, namely, (P)-helicene-BN and (M)-helicene-BN. [123] The design is based on merging the helical chirality with B/N/S-inserted PAH skeleton. The designed emitter exhibited narrowband green emission with an FWHM of 46 nm.…”
Section: Green Mr-tadf Emittersmentioning
confidence: 99%